Seed-mediated RNA interference of androgen signaling and survival networks induces cell death in prostate cancer cells - Joshua M. Corbin; Constantin Georgescu; Jonathan D. Wren; Chao Xu; Adam S. Asch; Maria J. Ruiz-Echevarría (Elsevier, 2021)
Resistance to anti-androgen therapy in prostate cancer (PCa) is often driven by genetic and epigenetic aberrations in the androgen receptor (AR) and coregulators that maintain androgen signaling activity. We show that specific small RNAs downregulate expression of multiple essential and androgen receptor-coregulatory genes, leading to potent androgen signaling inhibition and PCa cell death. Expression of different short hairpin/small interfering RNAs (sh-/siRNAs) designed to target TMEFF2 preferentially reduce viability of PCa but not benign cells, and growth of murine xenografts. Surprisingly, this effect is independent of TMEFF2 expression. Transcriptomic and sh/siRNA seed sequence studies indicate that expression of these toxic shRNAs lead to downregulation of androgen receptor-coregulatory and essential genes through mRNA 3' UTR sequence complementarity to the seed sequence of the toxic shRNAs. These findings reveal a form of the "death induced by survival gene elimination" mechanism in PCa cells that mainly targets AR signaling, and that we have termed androgen network death induced by survival gene elimination (AN-DISE). Our data suggest that AN-DISE may be a novel therapeutic strategy for PCa.